My daddy! my one and only! Ang daddy ko! ang nag-iisa at kaisa-isa! - Gagatiga, Zarah (Lampara books, 2013)
"There is this child telling a story about his daddy. What his daddy does for him and with him is more important than material gifts. There are many good things his daddy can do, that is why he has no reason to wish for another daddy."